Selected Factors of Innate Immunity in Healthy Individuals with S. aureus Nasal Carriage - Karpiński, Tomasz M.; Żaba, Zbigniew; Chudzicka-Strugała, Izabela; Szkaradkiewicz, Anna K.; Jaworska, Agata; Zeidler, Agnieszka; Andrzejewska, Ewa; Szkaradkiewicz, Andrzej (Frontiers in Microbiology, 2016)
Nasal carriage of Staphylococcus aureus represents a well-defined factor of risk involving community and hospital-acquired infections. Recently a significance of several host factors has been pointed out and, in particular, of immune determinants in nasal S. aureus colonisation. Therefore, this study aimed at analysis of manifestation involving manifestation in the nasal secretions of important components of the host innate immunity - human beta-defensin-2 (HBD-2), lysozyme (Ly) and interferon-gamma (IFN-γ) in healthy individuals and in persons with persistent carriage of S. aureus. The studies were conducted in two groups of healthy volunteers, encompassing non-carriers (group 1) or persistent carriers of S. aureus (group 2). Elisa assays were employed to evaluate levels of HBD-2, Ly and IFN-γ in nasal secretions of the examined donors. In S. aureus carriers a significant variability of HBD-2 levels was detected, corresponding to, respectively, the high (averaging at 1.46 ng/ml) and the low (averaging at 0.13 ng/ml) secretory response of the defensin. The level of Ly in S. aureus carriers averaged at 1.46 µg/ml and it manifested no significant difference as compared to that noted in non-carriers. In turn, concentrations of IFN-γ in nasal secretions in the group of carriers of S. aureus amounted on the average to 81.7 pg/ml and they were 1.3-fold higher that in the group of non-carriers. The obtained results allow to conclude that IFN-γ secretion by the nasal cavity-colonising S. aureus remains quantitatively insufficient to eliminate the pathogen. Nevertheless, a significant increase in levels of this host factor may be important for restriction of the staphylococcal colonisation and protection against development of an invasive infection. In turn, the role of HBD-2 and Ly in inactivation of the colonizing S. aureus remains doubtful.